Energy Reporting Practices among Top Energy Intensive Industries in Malaysia - Tasrip N.E.; Husin N.M.; Alrazi B. (Institute of Physics Publishing, 2023)
Energy utilization; Content analysis; Corporate social responsibilities (CSR); Energy intensive companies; Energy intensive industries; Environmental reporting; Malaysian governments; Reduce energy consumption; Response of energy; Social aspects; corporate social responsibility; electricity industry; energy market; energy use; environmental economics; environmental education; government; industrial enterprise; industrial practice; information; Malaysia